Determinan Pending Claim Badan Penyelenggara Jaminan Sosial Kesehatan di Rumah Sakit - Nayada Ilfania Arokhta Yunifa; Achmad Jaelani Rusdi; Lilik Afifah (Syntax Corporation Indonesia, 2025)
Pending claims are a problem that still often occurs in Indonesia, where many hospitals face obstacles in the BPJS Kesehatan claim process. This problem can have a significant impact on the quality of health services. This study aims to analyze the factors that cause BPJS Kesehatan pending claims in hospitals. The method used is literature review by searching for articles through the Google Scholar database in the last five years. The study follows PRISMA guidelines and uses the PICO framework to determine inclusion and exclusion criteria. The keywords used in the search involve the operator's boolean: